Multisystem proteinopathies (MSPs) and MSP‐like disorders: Clinical‐pathological‐molecular spectrum. Issue 4 (1st March 2023) - Chompoopong, Pitcha; Oskarsson, Björn; Madigan, Nicolas N.; Mirman, Igal; Martinez‐Thompson, Jennifer M.; Liewluck, Teerin; Milone, Margherita
Abstract: Objectives: Mutations in VCP, HNRNPA2B1, HNRNPA1, and SQSTM1, encoding RNA‐binding proteins or proteins in quality‐control pathways, cause multisystem proteinopathies (MSP). They share pathological findings of protein aggregation and clinical combinations of inclusion body myopathy (IBM), neurodegeneration [motor neuron disorder (MND)/frontotemporal dementia (FTD)], and Paget disease of bone (PDB). Subsequently, additional genes were linked to similar but not full clinical‐pathological spectrum (MSP‐like disorders). We aimed to define the phenotypic‐genotypic spectrum of MSP and MSP‐like disorders at our institution, including long‐term follow‐up features. Methods: We searched the Mayo Clinic database (January 2010–June 2022) to identify patients with mutations in MSP and MSP‐like disorders causative genes. Medical records were reviewed. Results: Thirty‐one individuals (27 families) had pathogenic mutations in: VCP ( n  = 17), SQSTM1 + TIA1 ( n  = 5), TIA1 ( n  = 5), MATR3, HNRNPA1, HSPB8, and TFG ( n  = 1, each). Myopathy occurred in all but 2 VCP ‐MSP patients with disease onset at age 52 (median). Weakness pattern was limb‐girdle in 12/15 VCP ‐MSP and HSPB8 patient, and distal‐predominant in other MSP and MSP‐like disorders. Twenty/24 muscle biopsies showed rimmed vacuolar myopathy. MND and FTD occurred in 5 (4 VCP, 1 TFG ) and 4 (3 VCP, 1 SQSTM1 + TIA1 ) patients, respectively. PDB manifested in 4 VCP ‐MSP. Diastolic dysfunction occurred in 2 VCP ‐MSP. After 11.5 years (median) from symptom onset, 15 patients ambulated without gait‐aids; loss of ambulation ( n  = 5) and death ( n  = 3) were recorded only in VCP ‐MSP. Interpretation: VCP ‐MSP was the most common disorder; rimmed vacuolar myopathy was the most frequent manifestation; distal‐predominant weakness occurred frequently in non‐ VCP ‐MSP; and cardiac involvement was observed only in VCP ‐MSP.